Africa calling [African wireless connection]. - Mbarika, V.W.A (IEEE spectrum)
It might come as a surprise that sub-Saharan Africa is now the world's fastest growing wireless market. The rate of growth for the entire continent has been more than 58% per year, compared with the almost 22% annual growth rate in America. This development is primarily attributed to the fact that Africa's landline networks and institutions are inadequate and that growing political stability has begun to attract more foreign investments to the region. Notwithstanding the substantial increase in complementary service jobs brought about by the wireless boom, the African government is urged to provide basic financial management training programs for vendors, especially kiosk owners who need help to look beyond their immediate financial gains to a sustainable future. African regulators are also urged to develop strategies to promote local investments in the wireless arena, as well as in other telecommunications sector.